2015
DOI: 10.1002/cctc.201500560
|View full text |Cite
|
Sign up to set email alerts
|

Dioxomolybdenum Complexes as Excellent Catalysts for the Deoxygenation of Aryl Ketones to Aryl Alkenes

Abstract: This work describes a new methodology for the selective deoxygenation of aryl ketones to the corresponding aryl alkenes catalyzed by dioxomolybdenum complexes using silanes as reducing agents. The best results were obtained with the system PhSiH3/MoO2Cl2(H2O)2 (5–10 mol %), which was very efficient for the deoxygenation of a large variety of aryl ketones to alkenes in excellent yields. This new methodology has the advantages of using an inexpensive, environmentally friendly, easily prepared, and air‐stable cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 36 publications
(24 reference statements)
1
9
0
Order By: Relevance
“…Similarly to our observations in the deoxygenation reactions of ketones to the corresponding alkenes described in our previous work, also in this study the best results were obtained with the dioxidomolybdenum complexes [MoCl 2 O 2 (H 2 O) 2 ], [MoCl 2 O 2 ], [MoCl 2 O 2 (DMSO) 2 ], and [MoCl 2 O 2 {(4‐ClPh) 2 SO} 2 ]. In contrast, only a moderate yield of xanthene (52 %) was observed in the reaction catalyzed by [MoCl 2 O 2 (Bipy)] (10 mol‐%) (Table , entry 6), and low yields of xanthene were isolated in the presence of the dioxido complexes [MoO 2 (acac) 2 ] (10 mol‐%), [MoCl 2 O 2 (OPPh 3 ) 2 ] (10 mol‐%), and [MoCl 2 O 2 (DMF) 2 ] (10 mol‐%) (Table , entries 7–9).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Similarly to our observations in the deoxygenation reactions of ketones to the corresponding alkenes described in our previous work, also in this study the best results were obtained with the dioxidomolybdenum complexes [MoCl 2 O 2 (H 2 O) 2 ], [MoCl 2 O 2 ], [MoCl 2 O 2 (DMSO) 2 ], and [MoCl 2 O 2 {(4‐ClPh) 2 SO} 2 ]. In contrast, only a moderate yield of xanthene (52 %) was observed in the reaction catalyzed by [MoCl 2 O 2 (Bipy)] (10 mol‐%) (Table , entry 6), and low yields of xanthene were isolated in the presence of the dioxido complexes [MoO 2 (acac) 2 ] (10 mol‐%), [MoCl 2 O 2 (OPPh 3 ) 2 ] (10 mol‐%), and [MoCl 2 O 2 (DMF) 2 ] (10 mol‐%) (Table , entries 7–9).…”
Section: Resultssupporting
confidence: 89%
“…After this, our group developed another very efficient method for the selective deoxygenation of aryl ketones to aryl alkenes using the inexpensive and environmental friendly catalyst [MoCl 2 O 2 (H 2 O) 2 ], with PhSiH 3 as reducing agent . During the development of this method we obtained a very interesting result in the reaction of flavone, a natural product, which allowed the conversion of the carbonyl group into a methylene group in 80 % yield [Equation ].…”
Section: Introductionmentioning
confidence: 99%
“…However their conversion into α‐aryl ketone is sparsely reported, despite the central importance of α‐aryl ketones as key intermediate for various important compounds viz. diarylisoxazoles, stilbenes and anthranilodinitrile etc as well as it′s application in pharmaceuticals and as bioactive molecules.…”
Section: Methodsmentioning
confidence: 99%
“…20 Based in that experience and the related deoxygenation of sulfoxides with glycerol, 21 we selected easily and conveniently prepared MoO 2 Cl 2 (dmso) 2 as catalyst, 22 for exploring the oxidative cleavage of benzopinacol (1,1,2,2-tetraphenylethane-1,2-diol) with DMSO (Table 1). 23 After some 70 experimentation we found that under microwave irradiation and using toluene as solvent at 130 ºC only one equiv. of DMSO was needed for complete cleavage of the model diol (entries 12).…”
mentioning
confidence: 99%
“…The E factor for the oxidative cleavage of 2,3-diphenylbutane-2,3-diol, selected as model, under the optimized microwave heating conditions is 50.1 (including the organic solvent employed for the extraction). Notably, the E factor calculated for the same 70 substrate under the recycling conditions (Scheme 1), where the amount of solvent employed for the extraction was optimized, dropped to 11.2. 28 These values are in the range of typical E factors of processes in fine-chemical companies and pharmaceutical industries.…”
mentioning
confidence: 99%